Evaluation of calculation models for the thermal conductivity of soils. (May 2018) - Zhang, Mingyi; Bi, Jun; Chen, Wenwu; Zhang, Xiyin; Lu, Jianguo
Abstract: In the study, a model matrix, based on the combinations of 1 thermal conductivity model for saturated soils ( λ sat ), 4 thermal conductivity models for dried soils ( λ dry ) and 4 Kersten number models for soils ( K e ), was proposed to calculate the thermal conductivity of soils. 16 calculation models were included in the matrix. The matrix could be used to investigate the effects of the λ dry models and K e models on the calculational results of the 16 calculation models for the thermal conductivity of soils. The matrix was evaluated by 40 Canadian soils, and it is found that the He et al. model for λ dry performs best among the 4 λ dry models, the Côté and Konrad model for K e performs best among the 4 K e models. It also shows that the results of the calculation models in the matrix are different significantly, but the JCM (combination of the geometric mean model for λ sat, the Johansen model for λ dry, and the Côté and Konrad model for K e ) performs best among the calculation models for the thermal conductivity of soils. The effects of the λ dry models and K e models on the calculational results of calculation models for the thermal conductivity were evaluated by the modified difference index (MDI), showing that the K e models have much larger effect on the calculational results than the λ dry models. Besides, the calculation models containing the Côté and Konrad model for K e were recommended to calculate the thermal conductivity of soils for its high accuracy.